Representing academic identities in email: content and structure of Automatic Signatures. (2nd September 2021) - Gesuato, Sara; Bianchi, Francesca
ABSTRACT: This paper analyses the automatic email signatures (ASs) of 200 academics. Qualitative and quantitative analyses of the ASs reveal that they are often written in one language, and only occasionally in two, English being a frequent choice. The ASs contain information with a primarily identificatory function, and occasionally with a promotional and socialising function. Despite the absence of clearly compulsory components, a typical structure can be identified in the ASs, which includes a specification of the writers' identity, reference to their affiliation, mention of their achievements, and an indication on how they can be reached. Like other academic texts, the ASs examined are places of self-categorisation and self-identification, tools for presenting one's professional identity, which are developing as sites of self-promotion.